Investigation of the influence of transport from oil and natural gas regions on elevated ozone levels in the northern Colorado front range. (1st February 2017) - Evans, Jason M.; Helmig, Detlev
ABSTRACT: The Northern Colorado Front Range (NCFR) has been in exceedance of the ozone National Ambient Air Quality Standard (NAAQS) since 2004, which has led to much debate over the sources of ozone precursors to the region, as this area is home to both the Denver, CO, metropolitan area and the Denver–Julesburg Basin, which has experienced rapid growth of oil and natural gas (O&NG) operations and associated emissions. Several recent studies have reported elevated levels of atmospheric volatile organic compounds (VOCs) as a result of O&NG emissions and the potential for significant ozone production from these emissions, despite implementation of stricter O&NG VOC emissions regulations in 2008. Approximately 88% of 1-hr elevated ozone events (>75 ppbv) occur during June–August, indicating that elevated ozone levels are driven by regional photochemistry. Analyses of surface ozone and wind observations from two sites, namely, South Boulder and the Boulder Atmospheric Observatory, both near Boulder, CO, show a preponderance of elevated ozone events associated with east-to-west airflow from regions with O&NG operations in the N-ESE, and a relatively minor contribution of transport from the Denver Metropolitan area to the SE-S. Transport from upwind areas associated with abundant O&NG operations accounts for on the order of 65% (mean for both sites) of 1-hr averaged elevated ozone levels, while the Denver urban corridor accounts for 9%. These correlations contribute to mounting evidence that air transport from areas with O&NG operation has a significant impact on ozone and air quality in the NCFR. Implications : This article builds on several previous pieces of research that implied significant contributions from oil and natural gas emissions on ozone production in the Northern Colorado Front Range. By correlating increased ozone events with transport analyses we show that there is a high abundance of transport events with elevated ozone originating from the Denver–Julesburg oil and natural gas basin. These findings will help air quality regulators to better assess contributing sources to ozone production and in directing policies to curb ozone pollution in this region.